Basic researchUpregulated expression of RANKL on bone marrow stromal cells can stimulate osteoclast precursors to mature into functional osteoclasts and promote survival of myeloma cells - Jinxiang, Fu; Jianhua, Zhang; Xiaohui, Zhang; Yu, Sun (Archives of Medical Science, 2008)
Introduction: Increased expression of receptor activator of NF-kB ligand (RANKL) and/or RANK may be involved in the excessive bone resorption observed in Multiple myeloma (MM). This report describes effects of myeloma cells on the differentiation of osteoclast precusors (pOCs) into OCs in different culture systems in vitro and the interaction between OCs and myeloma cells. Material and methods: We provide evidence that the pOCs matured in medium containing recombinant human macrophage colony-stimulating factor (rhM-CSF) and RANKL. Co-culture of RPMI 8266and XG1 in a direct contact manner, MM cells promoted the pOCs to differentiate into mature OCs in medium with rhM-CSF and in turn the MM cells proliferated and grew well in present of mature OCs. Results: In vitro assays showed that MM cells induced bone marrow derived monoclear cells to differentiate into adherent tartrat-resistant acid phosphatase positive multinucleated cells, indicative of the formation of functional OCs. The OCs supported the survival and proliferation of those MM cells in culture without serum by the way to protect them from apoptosis and dying, but they can’t reverse the apoptosis induced by dexamethasone in vitro. The RT-PCR assays revealed that the RPMI8266, XG1 and XG7 cells didn’t express mRNA transcripts for a membrane-bound and a secreted form of RANKL. MM cells RPMI8266 and XG1 trigged increased RANKL and decreased OPG expression of BMSCs in co-culture system. Conclusions: Our results indicate that OCs and MM cells were dependent each other for their growth and survival and support the data of role of the microenvironment in tumor sustenance and progression.